Farmers’ Perceptions of Agricultural Land Values in Rural Pakistan (The Pakistan Development Review, 2015)
Pakistan’s agriculture sector is crucial because it is responsible for providing food, shelter, and clothing to a massive population of 180 million people which is growing at a rate of 2 percent per annum. Land is a valuable asset and a symbol of prestige for the rural population in Pakistan. According to the recent Pakistan Economic Survey of 2013- 14, the agriculture sector contributes around 21 percent to GDP and provides employment for around 45 percent of the work force, who are primarily based in rural areas. The total geographic area of Pakistan is approximately 79.6 million hectares. Around 27.7 percent of Pakistan’s land is currently under cultivation and the cultivatable waste lands offer good possibilities for crop production. The total cropped area of Pakistan increased from 21.82 million hectares in 1990-91 to 22.72 million hectares in 2010-11 [Agricultural Statistics of Pakistan (2010-11)] and the total population of Pakistan increased from 118 million to 175 million during the same time period. Similarly the tenancy status of land management and land ownership pattern has changed over time. For example, large landowners are shifting their preferences from managing their land on their own towards leasing or sharecropping the land to be managed by others [Agricultural Census (2010)].